Samsung Galaxy Tabs for dummies - Gookin, Dan. (For Dummies, 2014)
Blast into the Samsung Galaxy and experience your tablet in a whole new way. Gookin helps you get the most out of your Galaxy Note or Galaxy Tab and all its amazing features |c Sources other than Library of Congress.